Comparison of morphological characters, flowering phenology and essential oils of two accessions of Cananga (Cananga odorata var. fruticosa) - MUTMAINNATUN NAFIS RABI’ATUN NA’IMAH; ANI KURNIAWATI; KRISANTINI KRISANTINI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Na’imah MNR, Kurniawati A, Kisantini. 2024. Comparison of morphological characters, flowering phenology and essential oils of two accessions of Cananga (Cananga odorata var. fruticosa). Biodiversitas 25: 801-810. The Cananga flowers are well-known in various regions of Indonesia as a raw material for essential oils and flower decorations. This study aims to compare the characteristics of two varieties of Cananga originating from Kediri and Cipanas. Both types of Cananga were cultivated in the Institut Pertanian Bogor (IPB) Cikabayan experimental field. Observation was conducted on leaf and flower characteristics, flowering phenology, and essential oil content. The research shows that the Kediri accession exhibited brownish-red leaf petioles, brownish-red branches, and dark brown stems. In contrast, the Cipanas accession had green leaf stalks, green branches, and light brown stems. The flowering phenology of the Kediri accession spanned from the emergence of flower buds to the End stage, lasting 35 days, while the Cipanas accession's flowering period extended for 25 days. The Kediri accession's flowers have more petals and are longer and heavier than the Cipanas accession. The highest essential oil content of the Cipanas accession occurred at the 50% full flowering stage, reaching 0.92%, and gradually decreased as the flowering progressed. In comparison, the Kediri accession oil content is the highest at the end of the flowering stage, with a peak of 0.61%. The highest compound in the Kediri accession is all-trans-Farnesol acetate 14,24%, ?-Copaene 12.23%, and Caryophyllene 15.92%. Meanwhile, in the Cipanas accession, the highest compound content was linalool 18.74% and caryophyllene 16.00%.